2017
DOI: 10.4310/mrl.2017.v24.n4.a11
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Lipschitz embedding of the generalized Grushin plane into Euclidean spaces

Abstract: We show that, for all α ≥ 0, the generalized Grushin plane Gα is bi-Lipschitz homeomorphic to a 2-dimensional quasiplane in the Euclidean space R [α]+2 , where [α] is the integer part of α. The target dimension is sharp. This generalizes a recent result of Wu [22].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…), set s 0 = − log 4/ log p 0 , and fix s ∈ [1, s 0 ). It is well-known that there exists a (1/s 0 )-bi-Hölder homeomorphism Φ : [0, 1] → S p ; e.g., see [BH04,RV17].…”
Section: Examplesmentioning
confidence: 99%
“…), set s 0 = − log 4/ log p 0 , and fix s ∈ [1, s 0 ). It is well-known that there exists a (1/s 0 )-bi-Hölder homeomorphism Φ : [0, 1] → S p ; e.g., see [BH04,RV17].…”
Section: Examplesmentioning
confidence: 99%
“…These facts, combined with a point of density argument, prevent any bilipschitz embedding of G 2 α into R α . By generalizing the construction in [27], Romney and Vellis [20] recently showed that G 2 α can be bilipschitzly embedded into R 2+ α for each α > 0, where α is the integer part of α.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of bilipschitz embedding of the Grushin plane G 2 α into R 3 has been proved in [27] and [20] for 0 < α 1 < 2; see the discussion in Section 1.1.…”
Section: Bilipschitz Parametrization and Embedding Of Grushin Spacesmentioning
confidence: 99%
“…Let β = 1−ǫ and let Y = {(0, v) : v ∈ R}. There exists a global bi-Lipschitz map Γ : [20,Cor. 1.3] in terms of our new notation for Grushin-type surfaces.…”
Section: For the Last Inequality Notice Thatmentioning
confidence: 99%
“…This shows that Γ is bi-Lipschitz as a mapping from the ( Y , β + β − ββ)-Grushin plane to the (Y, β)-Grushin plane. The ( Y , β + β − ββ)-Grushin plane is isometric (up to rescaling) to the usual [20].…”
Section: For the Last Inequality Notice Thatmentioning
confidence: 99%